Competition over Cursed Consumers - Alessandro Ispano; Peter Schwardmann (Center for Economic Studies and ifo Institute (CESifo), 2018)
We model firms' quality disclosure and pricing in the presence of cursed consumers, who fail to be sufficiently skeptical about undisclosed quality. We show that neither competition nor the presence of sophisticated consumers necessarily protect cursed consumers from being exploited. Exploitation arises if markets are vertically differentiated, if there are few cursed consumers, and if average product quality is high. Three common policy measures aimed at consumer protection, i.e. mandatory disclosure, third party disclosure and consumer education may all increase exploitation and decrease welfare. Even where these policies improve overall welfare, they often lead to a reduction in consumer surplus.
Keywords: C72; D03; D82; D83; 330; naïve; cursed; disclosure; consumer protection; labeling; competition